Football Match Result Prediction Using Machine Learning and Binary Model Fusion - da S. Souza, Douglas; S. de Araújo, Leandro (Anais Estendidos do Simpósio Brasileiro de Banco de Dados (SBBD); 2026: Anais Estendidos do XLI Simpósio Brasileiro de Bancos de DadosDO - 10.5753/sbbd_estendido.2026.249742, 2026)
This paper investigates English Premier League match result prediction using complementary machine learning approaches: direct multiclass classification, temporal goal forecasting, Isolation Forest-based binary anomaly detection, and simple binary decision-level fusion. Experiments were conducted on EPL data from the 2006–07 to the 2024–25 seasons using an expanding-window walk-forward validation protocol. Results show that betting odds concentrate most of the predictive information in direct classification, while temporal goal forecasting provides useful numerical estimates but does not necessarily improve outcome reconstruction. Isolation Forest underperforms supervised models in the binary setting, and binary fusion does not outperform the best individual model.